Physiological responses of Physalis angulata L. grown under molybdenum rates in hydroponic system - Souza Teles Fonseca, Josandra; Claudinéia Regina; Nascimento , Marilza Neves do; Leite, Romeu da Silva; Silva, Aritana Alves da; Vilanova, Thicyanne Oliveira (Comunicata Scientiae, 2023)
Studies on plant development evaluating the effects of molybdenum (Mo) applications are important for nutritional management in crops, such as Physalis angulata L. crops. Therefore, the objective of this work was to evaluate the responses of Physalis angulata grown under molybdenum rates in hydroponic system. The experiment was conducted in a completely randomized design, with 12 replications and five treatments (Mo rates: 0, 0.005, 0.01, 0.015, and 0.02 mg dm-3 of H2MoO*4H2O). Chlorophyll content, gas exchange parameters, nitrate reductase activity, total protein content, dry weights of leaves, stems, and roots, and root to shoot ratio were evaluated. Supplying Mo (0.02 mg dm-3) provided gains in biomass, which is connected to the total plant weight and total chlorophyll content. The nitrate reductase activity in leaves and roots was stimulated by Mo supplementation; the highest activity was found in the roots. Photosynthetic rate (0.010 mg dm-3) and water use efficiency (0.015 mg dm-3) were favored by increases in Mo rates. The results showed that application of molybdenum as a fertilizer resulted in positive effects on biomass gain, chlorophyll content, photosynthetic rate, and water use efficiency for P. angulata plants grown in hydroponics.